The Mystery behind Relaxation Therapy: Adieu to Premenstrual Syndrome - Jose, Ancy; Nayak, Sabitha; Kamath, Neetha; M., Nalini (Journal of Health and Allied Sciences NU, 2021)
Premenstrual syndrome (PMS) is a very common condition leading to physical, emotional, and psychological distress in females during their reproductive years. Researchers found that as many three of every four menstruating women have experienced some form of PMS. Although the severity of this problem is great, a lot of confusion exists in both medical and lay communities about what is and is not effective for the treatment of PMS. It has a wide variety of signs and symptoms and it may tend to recur in a predictable pattern. The physical and emotional changes experienced with PMS may vary from just slightly noticeable to very intense. Lifestyle adjustments in every kind can help to reduce or manage the signs and symptoms of PMS. Apart from all these, one of the most beneficial methods to reduce the difficulties of PMS is relaxation therapy which includes meditation, visualization, autogenic, Tai Chi, hydrotherapy, exercise, massage, aromatherapy, biofeedback, relaxation breathing, progressive muscle relaxation (Jacobson’s progressive relaxation therapy and The Mitchells progressive relaxation therapy) and yoga. Thus when remedies are available why not we celebrate the inborn power of relieving PMS in women.
Keywords: mood swings; premenstrual syndrome; relaxation therapy; premenstrual dysphoric disorder